2020
DOI: 10.1080/01616412.2020.1820698
|View full text |Cite
|
Sign up to set email alerts
|

The impact of botulinum toxin type A in the treatment of drooling in children with cerebral palsy secondary to Congenital Zika Syndrome: an observational study

Abstract: Objective:The main aim of this study was to determine the impact of botulinum toxin A (BTX-A) on severity and frequency of drooling in children with Cerebral Palsy (CP) secondary to Congenital Zika Syndrome (CZS). Methods: This is a prospective longitudinal observational study including 23 children who received bilateral injections of BTX in the parotid and submandibular glands. The Thomas-Stonell & Greenberg Drooling Severity and Frequency Scale was applied by a multidisciplinary team including Speech, Langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For example, the United Kingdom, as a country with relatively perfect social security, has set up special schools for children with CP, and professional therapists provide services every month [ 29 ]. A treatment center for CP has been established in the capital of Denmark, focusing on the assistance of children [ 30 , 31 ]. Family rehabilitation in the United States and Britain requires a family health care model that combines hospitals and families, emphasizing the treatment of the family as a unit [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the United Kingdom, as a country with relatively perfect social security, has set up special schools for children with CP, and professional therapists provide services every month [ 29 ]. A treatment center for CP has been established in the capital of Denmark, focusing on the assistance of children [ 30 , 31 ]. Family rehabilitation in the United States and Britain requires a family health care model that combines hospitals and families, emphasizing the treatment of the family as a unit [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that a few patients had side effects after injection, but most of them had mild to moderate transient adverse events. In this systematic review, six studies reported dysphagia as common adverse effects after the first injection, 12,18,19,22,28,31 one study reported speech problems. 22 All of these effects are fully reversible as the effect of botulinum toxin is transient.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the qualitative and quantitative analysis was conducted with eight clinical studies involving BoNT-A as the treatment of drooling in children. [12][13][14][15][16][17][18][19]…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations